4*3^x+1-9^x=27

Simple and best practice solution for 4*3^x+1-9^x=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4*3^x+1-9^x=27 equation:



4*3^x+1-9^x=27
We move all terms to the left:
4*3^x+1-9^x-(27)=0
We add all the numbers together, and all the variables
4*3^x-9^x-26=0
Wy multiply elements
12x-9^x-26=0
We move all terms containing x to the left, all other terms to the right
12x-9^x=26

You can always share this solution

See similar equations:

| -2(x-6)=14 | | 4*3^x+1-9x=27 | | 9x-1633x=20 | | -3x^2+3-8x=0 | | (x+9)2=9 | | 23=5-t | | ?2(3x?4)?x?3=33 | | t2-7t-8=0 | | 4(2x+1)-2x=-8 | | 0.25x+0.20(100-x)=21 | | 5-8x=12-7x | | H(t)=14+32t-16^2 | | 0.08(x+3000)=3840 | | x^+3x=70 | | (12x-53)+(6x+25)=180 | | 5(3x-3)=16 | | X^3+10x^2+24x-92=0 | | 2x=5×-30 | | 5x+12=9x+48 | | 6x36=72 | | 24-6x+32-4x=180 | | A=(15+x) | | 3(a+4)=6(a+2)-3a | | x+2x=192 | | y+5.7=8.44 | | 2(v-2)-5v=-1 | | -7x+52=2x-13 | | x-(9-2x)=0 | | x-(-2x)=0 | | 0.06(x-0.05)=0.06x+0.01 | | 3/4=6c | | 2(3n+3)=7(4n+6)+4 |

Equations solver categories